Dental cell sheet biomimetic tooth bud model. (November 2016) - Monteiro, Nelson; Smith, Elizabeth E.; Angstadt, Shantel; Zhang, Weibo; Khademhosseini, Ali; Yelick, Pamela C.
Abstract: Tissue engineering and regenerative medicine technologies offer promising therapies for both medicine and dentistry. Our long-term goal is to create functional biomimetic tooth buds for eventual tooth replacement in humans. Here, our objective was to create a biomimetic 3D tooth bud model consisting of dental epithelial (DE) – dental mesenchymal (DM) cell sheets (CSs) combined with biomimetic enamel organ and pulp organ layers created using GelMA hydrogels. Pig DE or DM cells seeded on temperature-responsive plates at various cell densities (0.02, 0.114 and 0.228 cells 10 6 /cm 2 ) and cultured for 7, 14 and 21 days were used to generate DE and DM cell sheets, respectively. Dental CSs were combined with GelMA encapsulated DE and DM cell layers to form bioengineered 3D tooth buds. Biomimetic 3D tooth bud constructs were cultured in vitro, or implanted in vivo for 3 weeks. Analyses were performed using micro-CT, H&E staining, polarized light (Pol) microscopy, immunofluorescent (IF) and immunohistochemical (IHC) analyses. H&E, IHC and IF analyses showed that in vitro cultured multilayered DE-DM CSs expressed appropriate tooth marker expression patterns including SHH, BMP2, RUNX2, tenascin and syndecan, which normally direct DE-DM interactions, DM cell condensation, and dental cell differentiation. In vivo implanted 3D tooth bud constructs exhibited mineralized tissue formation of specified size and shape, and SHH, BMP2 and RUNX2and dental cell differentiation marker expression. We propose our biomimetic 3D tooth buds as models to study optimized DE-DM cell interactions leading to functional biomimetic replacement tooth formation.